Modelling of Carburization Parameters Process for Low Carbon Steel - Abbas Khammas Hussein; Laith Kais Abbas; Jamal Jalal Dawood; Nadeen Jaafar Ismae (Engineering and Technology Journal, 2016)
This paper representsthe carburization parameters for steel (1020) using Desirability Function Analysis-DFA. The experiments were conducted using Taguchi (L9) orthogonal array. Carburization parameters such as carburization temperature, carburization time and tempering temperature were optimized by multi - response considerations depending onmicrohardnessand were rate measurements. The optimal carburizing parameters had been determined by composite desirability value obtained from desirability function analysis while significant contribution of parameter was determined by analysis of variance (ANOVA). The analyses results showed that optimal combination for higher hardness and lower wear rate were at (A2=920 oC, B2= 3 hours and C3=120 oC). Confirmation test was also conducted to validate the test results. Mathematical models for composite desirability, microhardness and rate wear were determined. Experimental results showed that the carburization performance can be improved effectively through desirability approach.